DNA barcoding of marine fish species in the waters surrounding Hainan Island, northern South China Sea - Zhang, Jinxia; Xu, Lei; Du, Feiyan; Tang, Quehui; Wang, Lianggen; Ning, Jiajia; Huang, Delian; Li, Yafang; Liu, Shuangshuang; Wang, Xuehui (Frontiers in Marine Science, 2023)
Hainan Island is encompassed within the shallow waters of the tropical continental shelf in China, which is recognized as a significant hotspot for fish biodiversity. Despite extensive research conducted on marine fish taxonomy surrounding Hainan Island, there remains a substantial gap between our current understanding and the actual fish diversity within this oceanic area. In this study, we employed DNA barcoding and molecular identification approaches to explore the species diversity and distribution pattern of marine fish in both the northern and southern sea areas of Hainan Island in the northern South China Sea. A total of 186 sequences were obtained from the collected marine fish samples in the two sea areas surrounding Hainan Island. Through DNA identification, it was confirmed that all 186 sequences corresponded to typical fish species found in the northern South China Sea, all sequences represented a total of 56 species, 47 genera, 34 families, and 17 orders. The average Kimura 2-parameter (K2P) distances within species, genus, family, order and class were 0.15%, 6.53%, 13.17%, 16.95% and 24.81%, respectively. Our investigation in the northern sea areas of Hainan Islands identified a total of 33 distinct species, while the southern sea areas exhibited 29 distinct species, with only 5 species found to be shared between both regions. These findings clearly indicate a significant disparity in the species composition of fish communities between the northern and southern sea regions.